Pemanfaatan Komik Webtoon Digital untuk Mengatasi Kesulitan Siswa dalam Menulis Cerita Pendek di SMP Negeri 24 Seluma - Nur Juwita, Trise; Andra, Vebbi; Friantary, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to address the difficulties faced by eighth-grade students at SMP Negeri 24 Seluma in writing short stories through the use of the Webtoon digital comic platform. The main problems faced by the students include a lack of ideas, difficulty in structuring the plot, and low motivation resulting from teaching methods that tend to be conventional. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. The research subjects were 28 eighth-grade students at SMP Negeri 24 Seluma. Data collection instruments included short story writing tests, student activity observation sheets, and documentation. Data analysis was conducted both quantitatively and qualitatively. The results of the study showed a significant improvement in the students’ short story writing skills. In the pre-cycle condition, the class achievement rate was only 32.1% (9 students) with an average score of 61.4. After the implementation of the Webtoon medium, in Cycle I, the class achievement rate increased to 60.7% (17 students) with an average of 70.2. A significant improvement occurred in Cycle II, with the classical mastery rate reaching 85.7% (24 students) and the average score jumping to 79.5. Based on these findings, it can be concluded that the use of Webtoon digital comics is effective in addressing students’ difficulties in writing short stories, stimulating their imagination through visual and textual stimuli, and increasing their active engagement in the learning process.